Izročilo o psoglavcih, volkodlakih, volčjem pastirju in Atili v mitski krajini SodražiceThe Lore about Dogheads, Werewolves, Wolf Herdsman and Attila in the Mythical Landscape of Sodražica - Češarek, Domen (Studia mythologica Slavica, 2015)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">In this article are presented and analysed local legends and myths about the supernatural being the Psoglavec (dogheaded/ Cynocephalus), the Werewolf, the Wolf Herdsman and Attila which survived in Ribnica, Slovenia and its surroundings. The name Psoglavec (dog-headed) is used as an insult for the inhabitants of the Sodražica community even today. These traditions have their roots in local myths, which are reflected in the mythological landscape. Different layers of myth with similar notions point towards a belief concept about the Wolf Herdsman, which was contaminated with other supernatural beings and historical figure of Attila.